2014
DOI: 10.1002/hfm.20559
|View full text |Cite
|
Sign up to set email alerts
|

Integrating ICTs and Supply Chain Management: The Case of Micro‐Sized Firms

Abstract: Information and Communication Technologies (ICTs) have changed the relationship between suppliers and buyers, and the nature of supply chain management. Previous research has studied this topic, but not from the point of view of micro-sized companies. Micro-sized companies are of critical importance for economies worldwide. Thus, in Europe 90% of companies are micro-enterprises and account for 53% of employment. This article presents a new perspective by studying the impact of the introduction of e-supply chai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 78 publications
0
9
0
Order By: Relevance
“…Petrick et al [47] indicates that ICT improves the production process, which directly affects the profits of the company in the short and long term. Llach and Alonso-Almeida [17] declare that the adoption and use of ICT help to redesign internal processes, and this means that they improve the efficiency of the Information Exchange in Production Control, causing activities to be fast, easy to handle, and more precise. To measure the impact of ICT in Production Control, the following five items are measured [17,47,48]: maintenance planning, performing tasks in the work area, delays in the process, introducing new products and services, and responding to market changes.…”
Section: Production Controlmentioning
confidence: 99%
See 2 more Smart Citations
“…Petrick et al [47] indicates that ICT improves the production process, which directly affects the profits of the company in the short and long term. Llach and Alonso-Almeida [17] declare that the adoption and use of ICT help to redesign internal processes, and this means that they improve the efficiency of the Information Exchange in Production Control, causing activities to be fast, easy to handle, and more precise. To measure the impact of ICT in Production Control, the following five items are measured [17,47,48]: maintenance planning, performing tasks in the work area, delays in the process, introducing new products and services, and responding to market changes.…”
Section: Production Controlmentioning
confidence: 99%
“…Gunasekaran et al [49] and Llach and Alonso-Almeida [17] claim that ICT adoption in managing the SC has strategic value because it provides competitive benefits in terms of efficiency and effectiveness in the production process, since it facilitates planning machine maintenance, provides solutions to delays, and streamlines the introduction of new processes. In addition, Shishodia et al [50] indicate that these ICT in production processes minimize human errors thanks to the automation of processes, which is reflected in the achievement of a better performance of the SC.…”
Section: Production Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, the work of Li and Lin [39] reveals that the management technology of education and training of personnel helps to integrate ICTs in SC activities. According to Fuentes et al [40] and Llach and Alonso-Almeida [41], education and training supports the sharing of adequate information and is a great support for the content of technology management, which helps meet the needs of clients and suppliers; however, it is the responsibility of senior management to carry out these training plans and follow up on them. Based on the above, the following hypothesis is proposed: Hypothesis 2 (H 2 ).…”
Section: Training In Ictmentioning
confidence: 99%
“…Recent studies have reported several benefits of the digitalized (digital) supply chain (DSC) over the traditional supply chain, including improved financial performance (Haoud and Hasnaoui, 2019;Youssef and El-Nakib, 2015), operational efficiency (Lu et al, 2012;Sharma and Bhagwat, 2006;Zhao and Jiang, 2013), customer satisfaction (Jiang and Zhao, 2014;Jonsson and Gunnarsson, 2005;Zhao and Jiang, 2013), employee skills (Llach and Alonso-Almeida, 2015;Srinivas, 2007) and supplier relations (Ranganathan et al, 2011;Zhao and Jiang, 2013), along with a reduction in operational and manufacturing cost (Haoud and Hasnaoui, 2019;Korpela et al, 2017;Di Vaio and Varriale, 2020), cycle time (Haoud and Hasnaoui, 2019) and errors (Youn et al, 2014). Realizing the significant advantages offered by the DSC on firm competitiveness, many firms have started the process of full or partial digitalization of their supply chain (Wu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%